2022
DOI: 10.1021/acsomega.2c01332
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-Catalyzed Multicomponent Synthesis of Highly Fluorescent Pyrimidine-Linked Imidazopyridines

Abstract: Herein, we report a metal-free one-pot three-component reaction of aryl methyl ketones, 2-aminopyridines, and barbituric acids for the synthesis of pyrimidine-linked imidazopyridines using a catalytic amount of molecular iodine in DMSO medium. This process involves a one-pot C–H oxidation, followed by the formation of one C–C and two C–N bonds. A wide variety of aryl methyl ketones and 2-aminopyridines were found to be suitable for this methodology. The UV and fluorescence properties of the synthesized product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…After that, β-iodoalkyl ketone ( III ) eliminated one molecular HI to successfully transform to the key intermediate 6 . The eliminated HI regenerates I 2 in the presence of DMSO for the next step reaction. , Under I 2 -promoted conditions, diselenide 2 can in situ generate R 2 Se + species, which can further produce seleniranium ion IV with 6 . Subsequently, the seleniranium ion IV undergoes nucleophilic attack of H 2 O to successfully obtain the desired product.…”
Section: Resultsmentioning
confidence: 99%
“…After that, β-iodoalkyl ketone ( III ) eliminated one molecular HI to successfully transform to the key intermediate 6 . The eliminated HI regenerates I 2 in the presence of DMSO for the next step reaction. , Under I 2 -promoted conditions, diselenide 2 can in situ generate R 2 Se + species, which can further produce seleniranium ion IV with 6 . Subsequently, the seleniranium ion IV undergoes nucleophilic attack of H 2 O to successfully obtain the desired product.…”
Section: Resultsmentioning
confidence: 99%
“…The use of catalytic amounts of flavin and iodine also helped to achieve this task (Scheme 5 (a)) [64] . Acharya and group accomplished this transformation using catalytic amounts of iodine in the presence of DMSO, which behaves as an oxidant as well as a solvent for this process (Scheme 5 (c)) [65] . Considering acetophenones, 2‐amino pyridine and 1,3‐dimethylbarbituric acid as the model substrates, they have achieved the desired products in substantial yields of up to 85 %.…”
Section: C−s Bond Formationmentioning
confidence: 99%
“…[64] Acharya and group accomplished this transformation using catalytic amounts of iodine in the presence of DMSO, which behaves as an oxidant as well as a solvent for this process (Scheme 5 (c)). [65] Considering acetophenones, 2-amino pyridine and 1,3-dimethylbarbituric acid as the model substrates, they have achieved the desired products in substantial yields of up to 85 %. This group noticed that the replacement of solvent with any other solvent and change in iodine sources lead to no product formation, which is manifesting the importance of the combination of iodine and DMSO as reagents.…”
Section: Cspà S Bond Formationmentioning
confidence: 99%
“…At first, the reaction between 2-picolyl amine and aryl aldehydes 1 via the I2/TBHP-mediated strategy formed intermediate 371 which undergoes iodination formed inter- Swadhin Swaraj Acharya et al reported metal-free one-pot three-component reaction for the synthesis of pyrimidine-linked imidazopyridine derivatives 375 by using aryl methyl ketones 18, 2-aminopyridines 363 and barbituric acids 62 in presence of catalytic amount of molecular iodine in DMSO medium at 110 °C (Scheme 69). [87] The reaction proceeds via one-pot C À H oxidation, followed by the formation of two C À N and one C À The key characteristics of this synthetic approach are a wide substrate scope, good to excellent yields, no need of column chromatographic purification. Moreover, the majority of the synthesized products also show extremely good to excellent fluorescence quantum yields.…”
Section: Synthesis Of Imidazolesmentioning
confidence: 99%
“…reported metal‐free one‐pot three‐component reaction for the synthesis of pyrimidine‐linked imidazopyridine derivatives 375 by using aryl methyl ketones 18 , 2‐aminopyridines 363 and barbituric acids 62 in presence of catalytic amount of molecular iodine in DMSO medium at 110 °C (Scheme 69). [87] The reaction proceeds via one‐pot C−H oxidation, followed by the formation of two C−N and one C−C bonds. The reaction proceeds via formation of an intermediate 376 and HI by the reaction between aryl methyl ketones 18 and iodine.…”
Section: Five‐membered Heterocyclic Compoundsmentioning
confidence: 99%